Role of Grb2 in myogenesis and epithelial-to-mesenchymal transition - Mitra, Payal (2016)
Grb2 is an adaptor protein whose SH2 domain has been shown to interact with phosphorylated tyrosine residues of activated receptors such as EGF and TGF-β and activate intracellular Ras/MAPK signaling pathway which controls the expression of genes required for biological processes such as proliferation and migration necessary for both myogenesis and EMT. Overexpression of Grb2 reduced the differentiation potential of C2C12 myoblasts significantly compared to the control indicating that Grb2 inhibits muscle differentiation. Overexpression of exogenous N-WASP in Grb2 overexpressing cells was found to rescue the inhibition of differentiation mediated by Grb2 indicating that inhibition of differentiation by Grb2 occurs through N-WASP. Alternatively, it was found that GRB2 expression increased significantly, during EMT, in lung adenocarcinoma cell line, A549. GRB2, even in the absence of TGF-β was found to cause drastic reduction in the E-Cadherin expression strengthening the hypothesis that Grb2 could play an independent role in controlling EMT. The expression of mesenchymal transcription factor, Snail was found to increase in GRB2 over expressing cells, before TGF-β stimulation suggesting that the reduction of E-Cadherin expression observed on GRB2 over expression may be mediated by Snail in A549 cells.